LC-MS-based metabolomics in profiling of drug metabolism and bioactivation - Feng Li; Frank J. Gonzalez; Xiaochao Ma (Elsevier, 2012)
Since metabolism significantly affects drug safety and efficacy, determining the metabolic profile of a drug is a critical part of drug development. The application of an LC-MS-based metabolomic approach has gained more widespread use in identifying drug metabolites, developing metabolic maps and lending clues to mechanisms of bioactivation. Thus, the LC-MS-based metabolomic approach is a powerful tool for profiling of drug metabolism and bioactivation.